Evaluation of a Robot-Assisted Therapy for Children with Autism and Intellectual Disability - Conti, Daniela; Trubia, Grazia; Buono, Serafino; Di Nuovo, Santo; Di Nuovo, Alessandro (Towards Autonomous Robotic Systems, 2018)
It is well established that robots can be suitable assistants in the care and treatment of children with Autism Spectrum Disorder (ASD). However, the majority of the research focuses on stand-alone interventions, high-functioning individuals and the success is evaluated via qualitative analysis of videos recorded during the interaction. In this paper, we present a preliminary evaluation of our on-going research on integrating robot-assisted therapy in the treatment of children with ASD and Intellectual Disability (ID), which is the most common case. The experiment described here integrates a robot-assisted imitation training in the standard treatment of six hospitalised children with various level of ID, who were engaged by a robot on imitative tasks and their progress assessed via a quantitative psycho-diagnostic tool. Results show success in the training and encourage the use of a robotic assistant in the care of children with ASD and ID with the exception of those with profound ID, who may need a different approach.